Ultrasmall copper-based nanoparticles for reactive oxygen species scavenging and alleviation of inflammation related diseases - Tengfei Liu; Bowen Xiao; Fei Xiang; Jianglin Tan; Zhuo Chen; Xiaorong Zhang; Chengzhou Wu; Zhengwei Mao; Gaoxing Luo; Xiaoyuan Chen; Jun Deng (Nature Communications)
Abstract Oxidative stress is associated with many acute and chronic inflammatory diseases, yet limited treatment is currently available clinically. The development of enzyme-mimicking nanomaterials (nanozymes) with good reactive oxygen species (ROS) scavenging ability and biocompatibility is a promising way for the treatment of ROS-related inflammation. Herein we report a simple and efficient one-step development of ultrasmall Cu5.4O nanoparticles (Cu5.4O USNPs) with multiple enzyme-mimicking and broad-spectrum ROS scavenging ability for the treatment of ROS-related diseases. Cu5.4O USNPs simultaneously possessing catalase-, superoxide dismutase-, and glutathione peroxidase-mimicking enzyme properties exhibit cytoprotective effects against ROS-mediated damage at extremely low dosage and significantly improve treatment outcomes in acute kidney injury, acute liver injury and wound healing. Meanwhile, the ultrasmall size of Cu5.4O USNPs enables rapid renal clearance of the nanomaterial, guaranteeing the biocompatibility. The protective effect and good biocompatibility of Cu5.4O USNPs will facilitate clinical treatment of ROS-related diseases and enable the development of next-generation nanozymes.